2014
DOI: 10.1186/s13046-014-0085-6
|View full text |Cite
|
Sign up to set email alerts
|

Transactivation of epidermal growth factor receptor through platelet-activating factor/receptor in ovarian cancer cells

Abstract: BackgroundWe previously identified platelet-activating factor receptor (PAFR) as being overexpressed in ovarian cancer and found that its ligand PAF evoked EGFR phosphorylation using the phospho-antibody microarray. Epidermal growth factor receptor (EGFR) are also overexpressed in ovarian cancer and contribute to the growth of ovarian cancer cells. Here, we investigated the mechanisms of crosstalk between PAFR and EGFR signaling in ovarian cancer cells to further determine whether the interaction between PAFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Ligand-dependent mechanisms involve the release of EGFR agonists through the cleavage and shedding of membrane-associated precursors by proteinases of the ADAM family [47]. Ligand-independent mechanisms have been reported to involve intracellular molecules, including Src family kinases and Pyk2 [48,49]. In the SKOV-3 cells, we observed that Src inhibitors abolished the PAF-induced phosphorylation of the EGFR.…”
Section: Discussionmentioning
confidence: 60%
“…Ligand-dependent mechanisms involve the release of EGFR agonists through the cleavage and shedding of membrane-associated precursors by proteinases of the ADAM family [47]. Ligand-independent mechanisms have been reported to involve intracellular molecules, including Src family kinases and Pyk2 [48,49]. In the SKOV-3 cells, we observed that Src inhibitors abolished the PAF-induced phosphorylation of the EGFR.…”
Section: Discussionmentioning
confidence: 60%
“…It has been reported to promote non-small cell lung cancer (NSCLC) progression and metastasis by initiating forward feedback loop between PAFR and STAT3 [ 10 ], and contributes to the malignant development of esophageal squamous cell carcinoma by stimulating PI3K/AKT activation [ 11 ]. PAFR can also induce chemotherapy resistance in ovarian cancer through transactivating of epidermal growth factor receptor (EGFR) [ 12 , 13 ]. In addition, LNCaP and PC-3 cells have been shown to produce PAF endogenously [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this, G-proteins like Ral, Rap as well as other signaling molecules like PLCγPLD are regulated by PAF-R [45,46] . In ovarian cancer cells PAF promotes cancer progression through EGFR/ERK transactivation pathway as well as activates PKC pathway, which couples with activated ERK [47] . FAK and Paxillin are activated following PAF induction in human endothelial cells [48] while in non-cancerous cell lines such as neutrophils [49] and eosinophils [50] , it activates various protein kinases such as G-protein kinase, PKC as well as tyrosine protein kinase [48] .…”
Section: Research Highlightmentioning
confidence: 99%